Histochemical demonstration of acetylcholinesterase in neuroblastoma. - Variend, S (1984)
The presence of acetylcholinesterase in the tumour cells of neuroblastoma has been shown by enzyme histochemistry. For comparison, some other tumours likely to be found in children and commonly presenting histologically as small cell tumours have also been studied. Acetylcholinesterase activity was seen in rhabdomyosarcoma, but, compared with neuroblastoma, the activity was focal and sparse. One Ewing's tumour and a lymphoblastic lymphoma were negative for the enzyme reaction. Some of the ultrastructural features of neuroblastoma are correlated with the presence of this enzyme. Acetylcholinesterase enzyme histochemistry may provide a useful adjunct in the distinction of neuroblastoma from other small cell tumours.